Modification of COMT-dependent pain sensitivity by psychological stress and sex. Issue 4 (April 2016) - Meloto, Carolina B.; Bortsov, Andrey V.; Bair, Eric; Helgeson, Erika; Ostrom, Cara; Smith, Shad B.; Dubner, Ronald; Slade, Gary D.; Fillingim, Roger B.; Greenspan, Joel D.; Ohrbach, Richard; Maixner, William; et al.
Abstract : Abstract: Catecholamine- O -methyltransferase ( COMT ) is a polymorphic gene whose variants affect enzymatic activity and pain sensitivity via adrenergic pathways. Although COMT represents one of the most studied genes in human pain genetics, findings regarding its association with pain phenotypes are not always replicated. Here, we investigated if interactions among functional COMT haplotypes, stress, and sex can modify the effect of COMT genetic variants on pain sensitivity. We tested these interactions in a cross-sectional study, including 2 cohorts, one of 2972 subjects tested for thermal pain sensitivity (Orofacial Pain: Prospective Evaluation and Risk Assessment) and one of 948 subjects with clinical acute pain after motor vehicle collision ( post–motor vehicle collision ). In both cohorts, the COMT high–pain sensitivity (HPS) haplotype showed robust interaction with stress and number of copies of the HPS haplotype was positively associated with pain sensitivity in nonstressed individuals, but not in stressed individuals. In the post–motor vehicle collision cohort, there was additional modification by sex: the HPS–stress interaction was apparent in males, but not in females. In summary, our findings indicate that stress and sex should be evaluated in association studies aiming to investigate the effect of COMT genetic variants on pain sensitivity. Abstract : Supplemental Digital Content Is Available in the Text. COMT genetic variants' effect on pain sensitivity is masked by stress and sex.